Trybunały – „Gacaca” w Rwandzie - Banasik, Katarzyna (Przegląd Prawno-Ekonomiczny, 2011)
Streszczenie dostępne wyłącznie w języku angielskim: Seventeen years have recently passed since the massacre in African Rwanda, regarded as the most shocking of the contemporary crimes of genocide. Not only an international tribunal ad hoc was established in order to sentence the perpetrators of this crime, but also special “Gacaca” tribunals, based on traditional local community courts, were created. These tribunals will soon complete their work. The time has come to summarise and evaluate their activities.